Photocatalytic Nitrogen Reduction: Challenging Materials with Reaction Engineering. Issue 9 (8th July 2021) - Ziegenbalg, Dirk; Zander, Judith; Marschall, Roland
Abstract: Ammonia is not only the most important chemical for fertilizer production, it has also gained much interest as a future hydrogen storage material. Besides the well‐known Haber–Bosch process to generate ammonia from elemental sources, new ways to convert nitrogen into ammonia have been investigated in the last decade for a decentralized production, including electrocatalytic and photocatalytic approaches. However, photocatalysis in particular suffers from stagnating materials development and unstandardized reaction conditions. In this Review, we shine light on recent materials and reaction engineering results for photocatalytic nitrogen reduction, putting an emphasis on the need to connect the activity of reported materials together with detailed reaction conditions and efficiencies. Photocatalytic nitrogen reduction is an emerging field that will certainly gain significant interest in the future as a sustainable pathway to generate green hydrogen and ammonia. The field will certainly strongly benefit from joint efforts with strong interactions between chemists, physicists and chemical engineers at a fundamental level. Abstract : A bright future ? Ammonia is of utmost importance for fertilizer production and recently gained interest as a future hydrogen storage material. However, photocatalytic production of ammonia suffers from stagnating materials development and unstandardized reaction conditions. This Review reports on recent materials and reaction engineering results, emphasizing the need to connect the activity of reported materials together with detailed reaction conditions and efficiencies. Research will strongly benefit from joint efforts between chemists, physicists and chemical engineers already at a fundamental level.